PERANCANGAN PUSAT REHABILITASI NARKOBA DENGAN PENDEKATAN ARSITEKTUR BIOFILIK DI SEPATAN - Adam Agnadhy Romansyah; Sri Kurniasih; Dody Kurniawan (MAESTRO, 2021)
Drug Rehabilitation Center is a place where someone who is addicted to drugs and illegal drugs wants to have self-awareness to recover and become a better human being. The applied biophilic architecture is also very suitable for accelerating the recovery of patients undergoing rehabilitation by uniting the elements of nature with humans. This Tangerang Regency area is one of the cases of drug addicts with a fairly large percentage, addicts include students and young people who still do not understand the dangers of drugs and illegal drugs.